Web portfolio design and applications - DiMarco, John, 1969- (Hershey, PA : Idea Group Publ., 2006)
'This book defines and gives an overview of the web portfolio and how it is being used in academic programs and professional scenarios'--Provided by publisher.
PS UNIKEB
Includes bibliographical references (p. 293-298) and index.
Keywords: Portfolios in education; Internet in education; World Wide Web